Multiple Network Interaction in Destination Competitive Advantage - hasan hasan; Retno Kusumaningrum (International Journal of Management, Business, and Social Sciences, 2022)
AbstractThis research provides a complete model of entrepreneurial learning enhancement and focus on the importance of multiple network interaction factors in creating a destination competitive advantage. The proposed model contributes to the theory of social exchange, learning organization, dynamic capability and knowledge management into the context of marketing strategies and sustainable tourism development. This study aims to determine how entrepreneurial learning will produce potential multiple network interactions to create a tourism competitive advantage. Key word :destination competitive advantage; multiple network interaction; crowdworking,